Inclusive and differential measurements of the t(t)over-bar charge asymmetry in pp collisions at root s=8 TeV - Khachatryan, V. (2016)
The t (t) over bar charge asymmetry is measured in proton-proton collisions at a centre-of-mass energy of 8 TeV. The data, collected with the CMS experiment at the LHC, correspond to an integrated luminosity of 19.7 fb(-1). Selected events contain an electron or a muon and four or more jets, where at least one jet is identified as originating from b-quark hadronization. The inclusive charge asymmetry is found to be 0.0010 +/- 0.0068 (stat)+/- 0.0037 (syst). In addition, differential charge asymmetries as a function of rapidity, transverse momentum, and invariant mass of the If system are studied. For the first time at the LHC, the measurements are also performed in a reduced fiducial phase space of top quark pair production, with an integrated result of -0.0035 +/- 0.0072 (stat) +/- 0.0031 (syst). All measurements are consistent within two standard deviations with zero asymmetry as well as with the predictions of the standard model. (C) 2016 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/). Funded by SCOAP(3).